Growth of InGaN quantum dots on GaN by MOVPE, employing a growth temperature nitrogen anneal - Oliver, R; Kappers, M; Rice, J; Smith, J; Taylor, R; Humphreys, C; Briggs, G (2003)
We have studied the growth of InGaN epitaxial layers on GaN by MOVPE (metal-organic vapour phase epitaxy), and have discovered that nanostructures may be formed if a flat epilayer is annealed in molecular nitrogen immediately after growth. The size and density of the nanostructures are shown to be dependent on the growth/anneal temperature. We demonstrated the quantum dot nature of our nanostructures by performing spatially resolved photoluminescence on samples that had been capped with a layer of GaN, grown at the same temperature as the InGaN epilayer. This revealed narrow, delta-function-like lines in the luminescence spectrum with full width at half maximum (FWHM) limited by the resolution of the spectrometer at 4.2 K. Measurement of the FWHM as a function of temperature revealed significant broadening above 20 K. (C) 2003 WILEY-VCH Vertag GmbH and Co. KGaA, Weinheim